Antimicrobial Resistance Pattern against E. coli and Salmonella spp. in Environmental Effluents (International Journal of Natural Sciences, 2016)
Hospitals (medical & veterinary) and slaughterhouse effluents were the most contaminating effluents and need to be paid more attention due to pathogenic bacteria related to animal and public health concern. Two bacterial isolates such as E. coli and Salmonella from six medical hospitals, five veterinary hospitals and five slaughter houses were isolated to find out the antibiotic resistance pattern by using disc diffusion method. The antibiotic resistance patterns of identified isolates showed that Ampicillin, Ciprofloxacin, Enrofloxacin, Pefloxacin, Colistin, Erythromycin, Oxytetracycline were 100%, Doxycycline was 83%, Gentamycin was 50% and Neomycin was 33% resistance to medical isolates and Ampicillin, Enrofloxacin, Pefloxacin and Erythromycin were 100%, Ciprofloxacin was 40%, Colistin was 60%, Doxycycline was 80%, Gentamycin was 20%; Neomycin and Oxytetracycline 80% resistance to veterinary hospital isolates and Ampicillin, Enrofloxacin, Ciprofloxacin, Pefloxacin, Colistin, Oxytetracycline, Gentamycin, Doxycycline and Erythromycin were 100% and Neomycin was 40% resistance to slaughter houses isolates of E. coli. The level of resistance of Salmonella positive isolates was found Ampicillin, Enrofloxacin, Pefloxacin, Gentamycin and Erythromycin to 100%, Ciprofloxacin was 67%, Oxytetracycline was 33% but Colistin and Neomycin was found sensitive to the isolates from both medical and veterinary hospital. Results indicated that hospitals and slaughter houses waste effluent has multiple-antibiotic resistance against E. coli and Salmonella.International Journal of Natural Sciences (2015), 5(2) 52-58